Implementation of a Methodology for the Detection of Biochemical Markers in Type 1 Tyrosinemia - Iovana Fuentes Cortés; Beliany Pacheco Suárez; Dulce María Charón Savón (Revista Finlay)
Foundation: hereditary tyrosinemia type I or hepato-renal tyrosinemia is an autosomal recessive disease caused by deficiency of the enzyme fumarylacetoacetate hydrolase. Due to its metabolic complexity, its confirmation requires a set of highly expensive methods. Objective: to implement a work methodology for the detection of marker metabolites of type 1 tyrosinemia. Method: a descriptive and cross-sectional study was carried out in a series of cases evaluated in the period from January 2021 to February 2023. As an initial examination, qualitative tests of α nitroso beta naphthol and 2,4 dinitrophenylhydrazine were carried out for the identification of tyrosine and α keto acids respectively. Then, the HPLC method was performed for the quantification of tyrosine and GC-MS for the determination of the chromatographic profile in urine as confirmatory techniques. Results: qualitative tests were positive for tyrosine and its metabolites, as well as for alpha keto acids. The organic acid profile showed elevated excretion of the disease marker metabolites in 8 cases, in which tyrosine quantification was performed, which were positive for suffering from the disease. Conclusions: the implementation of the methodology turned out to be a valuable tool in the early diagnosis of the disease.